How context influences the functionality of community‐level health governance structures: A case study of community health committees in Kenya. (13th February 2023) - Karuga, Robinson; Kok, Maryse; Mbindyo, Patrick; Otiso, Lilian; Macharia, Judy; Broerse, Jacqueline E. W.; Dieleman, Marjolein
Abstract: Community Health Committees (CHCs) are mechanisms through which communities participate in the governance and oversight of community health services. While there is renewed interest in strengthening community participation in the governance of community health services, there is limited evidence on how context influences community‐level structures of governance and oversight. The objective of this study was to examine how contextual factors influence the functionality of CHCs in Kajiado, Migori, and Nairobi Counties in Kenya. Using a case study design, we explored the influence of context on CHCs using 18 focus group discussions with 110 community members (clients, CHC members, and community health volunteers [CHVs]) and interviews with 33 health professionals. Essential CHC functions such as 'leadership' and 'management' were weak, partly because Health professionals did not involve CHCs in developing health plans. Community Health Committees were active in the supervision of CHVs, reviewing their household reports, although they did not utilise these data for making decisions. Resource mobilisation and evaluation of health programs were affected by the lack of administrative and operational support, such as training. Despite having influential membership, CHCs could not provide leadership and management functions. Health system actors perceived the roles of CHCs as service providers rather than structures for governance and oversight. Insufficient awareness of CHC roles among health professionals, lack of training and operational support for community‐based activities constrained CHCs' functionality and thus their role in community participation. While there are efforts to institutionalise community‐level governance structures for health at sub‐national level, there is a need to scale‐up these efforts countrywide. We recommend that community‐level governance structures be empowered, mandated, and provided with resources to take on the responsibility of overseeing community health services and exacting accountability from health providers. Key points: Selection of elite persons in community‐level health committees does not enhance the leadership roles in these committees. Legislation on community‐level health governance committees could enhance community participation in planning and managing health programs. Implementation of vertical health programs without the community participation contributes to missed opportunities for incorporating local knowledge into these programs. Community members and health professionals who implement community health services still do not understand the importance of community participation in making decisions in community health programs.